Inequalities in the Teaching Profession : A Global Perspective - Moreau, Marie-Pierre; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Countering the commonplace view of teaching as inclusive, this collection highlights the persistence of inequalities in the teaching profession. It explores the ways in which gender, ethnicity, social class and other identity markers shape teachers' experiences in a range of institutional and national contexts.
Keywords: Education; Educational sociology; Teaching; Gender identity in education; Social structure; Social inequality; Education and sociology; Sociology, Educational; Social justice; Human rights; Gender and Education; Social Structure, Social Inequality; Sociology of Education; Sociology of Education; Social Justice, Equality and Human Rights; Teaching and Teacher Education